2022
DOI: 10.1007/jhep08(2022)303
|View full text |Cite
|
Sign up to set email alerts
|

Heavy quarkonium dynamics at next-to-leading order in the binding energy over temperature

Abstract: Using the potential non-relativistic quantum chromodynamics (pNRQCD) effective field theory, we derive a Lindblad equation for the evolution of the heavy-quarkonium reduced density matrix that is accurate to next-to-leading order (NLO) in the ratio of the binding energy of the state to the temperature of the medium. The resulting NLO Lindblad equation can be used to more reliably describe heavy-quarkonium evolution in the quark-gluon plasma at low temperatures compared to the leading-order truncation. For phen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 74 publications
1
24
1
Order By: Relevance
“…Using such a strategy, in Ref. [35] we derived a GKSL equation that is accurate to order E/T and respects positivity. 1 This allows one to map the quantum master equation to a GKSL equation that can be solved using a stochastic unraveling called the quantum trajectories algorithm [35,61].…”
Section: The Quantum Master Equation For Heavy-quarkonium Evolutionmentioning
confidence: 99%
See 4 more Smart Citations
“…Using such a strategy, in Ref. [35] we derived a GKSL equation that is accurate to order E/T and respects positivity. 1 This allows one to map the quantum master equation to a GKSL equation that can be solved using a stochastic unraveling called the quantum trajectories algorithm [35,61].…”
Section: The Quantum Master Equation For Heavy-quarkonium Evolutionmentioning
confidence: 99%
“…In Refs. [35,37] it was found that the NLO OQS+pNRQCD framework provided a good description of existing experimental data from the ALICE, ATLAS, and CMS collaborations for both the nuclear modification factor, R AA , and elliptic flow, v 2 .…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations